HAMULI LEBAH MADU Apis (Hymenoptera: Apidae) PADA BEBERAPA KETINGGIAN DI SUMATERA BARAT - Jasmi, Jasmi (Sainstek : Jurnal Sains dan Teknologi, 2013)
Research of hamuli of Apis have done at altitude 0 to 1400 m, in West Sumatra from December 2009-July 2010. Bees have collected from fruits, coffee crop and side of forest which are distances about 200 metre for each altitude. They were identified in Laboratory of Animal Taxonomy, Departement of Biology, Faculty of Matematics and Sciences, Andalas University Padang. We found four Apis species from three subgenus. Subgenus Micrapis consisted of one species  that is A. andreniformis Smith. Subgenus Sigmatapis consisted of two specieses, A. cerana Enderlein and A. koschevnikovi Enderlein. SubgenusMegapis consisted of one species that is  A. dorsata Fabr. Number of hamuli of worker bee have been variated, depent on bee types and habitat. Number of hamuli of A. cerana between 13-22 (average 17.7), A. dorsata between 22-30 (average 26.53) and A. andreniformis between  8-12 (average  9.84).Key words: Apis, hamuli of worker, altitude difference